(3JUeje GdHQeLjGJ GdLGgRI hEfJGLgG (B/s - (3fUQ, MSf Hf CMeO eMehOs ((3LOI (B:s (3NhGQRe GdYdejI ddfTQ hGdJhRjY ,s, 2011)
(3gPG GdcJGH jQcR Ydi JUeje GdHQeLjGJ GdJYdjejI hEfJGLgG ceG jTcd EMOi GdeTGQcGJ GdYdejI aj EWGQ JWhjQ hJMOjK GdefGgL GdOQGSjI ddWdGH, ceG jgOa Edi JMOjO Ch GNJjGQ eQLY Ydej eJNUU jecf GdQLhY Edjg aj YedjI GdJOQjS, Ydi Cf jchf eSJhajG dehVhYGJ hYfGUQ NWI YdejI JSJWjY Cf JMbb GdCgOGa GdYdejI hGdJQHhjI GdJj Je JMOjOgG aj GdNWI GdOQGSjI GdehVhYI ef bHd GddLGf GdYdejI HGdLGeYI, hJhUj GdeGOI GdYdejI GdehLhOI Hjf WjGJ gPG GdcJGH Edi JMbjb gOajf QFjSjjf (B: (3ChdgeG (B: (3JMbjb GdeWdH GdedM aj Cf jQLY GdWGdH GdLGeYj(B-(3aj OQGSJg dCjI eGOI YdejI(B-(3Edi eQLY Ydej TGed jUdM dCf jMbb GdZQV GdYdej GdefhW HJCgjdg Edi OQLI GdeYde GdfGLM aj eLGd JNUUg, hKGfjgeG (B: (3GSJgOGa cGaI GdHGMKjf hGdegJejf HTFhf GdJYdje, hJUeje GdHQGeL GdJYdjejI NGUI, hbO LGAJ ehVhYGJ GdcJGH aj YOI ehVhYGJ (B: (3aJfGhd GdHGH GdChd JUeje GdJYdje, aj Mjf JfGhd GdHGH GdKGfj GSJNOGeGJ GdMGSH, CeG GdHGH GdKGdK GdEfJQfJ hOhQ GdeYde, hCNjQG LGA GdHGH GdQGHY djYQV GdJYdje hGdeHQeL, haj fgGjI GdcJGH PcQ GdeDda bGFeI GdeUGOQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B257.s
Keywords: (3GdJYdjes -- (3HQGeL GdMGShHs; (3GdhSGFd GdJYdjejIs -- (3GSJNOGes; (3GdhSGFd GdJYdjejIs -- (3JUeje s